Co‐Crystal of Paracetamol and Trimethylglycine Prepared by a Supercritical CO2 Anti‐Solvent Process. Issue 6 (6th April 2018) - Zhao, Ziyi; Liu, Guijin; Lin, Qing; Jiang, Yanbin
Abstract: Paracetamol (PCA) and trimethylglycine (TMG) were co‐crystallized and micronized by means of the supercritical anti‐solvent (SAS) process to improve the tabletability of PCA. The effects of operating conditions on particle properties were investigated in detail. Characterizations were performed to confirm the co‐crystal state of PCA‐TMG. The results indicated that the same crystal form with different crystal habits was prepared. The optimal PCA‐TMG co‐crystals presented a much larger tensile strength, higher drug content of PCA, and smaller particle size than those obtained using the ball milling (BM) process. The SAS‐processed PCA‐TMG co‐crystals showed an enhanced solubility, dissolution rate, and tableting performance compared to that of BM. Abstract : In order to enhance the tabletability of paracetamol, it was co‐crystallized with trimethylglycine and micronized by a supercritical anti‐solvent process which is a robust approach to fabricate co‐crystals. Its ability to produce micrometer‐sized co‐crystals with altered physicochemical properties is demonstrated, for improving drug potency and reducing its toxicity and side effects.